Extension of holomorphic mappings for several moving hypersurfaces - Si Duc Quang (Український математичний журнал, 2012)
We prove the big Picard theorem for holomorphic curves from a punctured disk into P ⁿ(C) with n + 2 hypersurfaces. We also prove a theorem on the extension of holomorphic mappings in several complex variables into a submanifold of P ⁿ(C) with several moving hypersurfaces. Доведено велику теорему Пiкара для голоморфних кривих iз проколотого круга в Pⁿ(C) iз n+2 гiперповерхнями. Також доведено теорему про продовження голоморфних вiдображень вiд декiлькох комплексних змiнних у пiдбагатовид Pⁿ(C) з декiлькома гiперповерхнями, що рухаються.